Performance assessment for the integrated green-gray-blue infrastructure under extreme rainfall scenarios - Zhang, Chen; Wang, Jia; Liu, Jiahong; Lv, Yongpeng; Chen, Jian; Yang, Zixin; Zhang, Nan (Frontiers in Ecology and Evolution, 2023)
Synergistic allocation of urban stormwater infrastructure is critical to flood risk prevention and control under extreme rainfall events. This study focuses on the interaction regularity of green, gray and blue infrastructure in the process of runoff retention and discharge under extreme rainfall scenario. Three strategies of gray infrastructure, green-gray infrastructure, and green-gray-blue infrastructure are proposed, to analyze the effectiveness of different scenarios on the flood risk control capability, and to determine the key influencing factors. The results show that green-gray-blue infrastructure demonstrates synergy in improving the efficiency of urban drainage system. Under gravity drainage conditions, the backwater jacking caused by high river water level would have a certain impact on the smooth discharge of stormwater runoff in urban drainage system. A sensitive range in the influence of water level on runoff control and drainage function, and an adaptive range in which the flood increases slightly with the water level rises were recognized based on the case study, which are notable rules in improving the synergistic effect of blue infrastructure in the integrated urban green-gray-blue infrastructure system.